2011
DOI: 10.1016/j.jbiomech.2010.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of in vivo anterior cruciate ligament strain during dynamic jump landing

Abstract: Despite recent attention in the literature, anterior cruciate ligament (ACL) injury mechanisms are controversial and incidence rates remain high. One explanation is limited data on in vivo ACL strain during high-risk, dynamic movements. The objective of this study was to quantify ACL strain during jump landing. Marker-based motion analysis techniques were integrated with fluoroscopic and magnetic resonance (MR) imaging techniques to measure dynamic ACL strain non-invasively. First, eight subjects’ knees were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
164
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(185 citation statements)
references
References 92 publications
17
164
4
Order By: Relevance
“…In both cases, in fact, stability or coaptation of the joint should be guaranteed, although in a different manner, by a synergic activity of both passive and active intra-and periarticular structures. This hypothesis is supported by recent findings that, during a highly dynamic motion such as the landing phase of a jump, showed that the ACL length decreases during flexion by an amount similar to that obtained in the present study [30].…”
Section: Discussionsupporting
confidence: 93%
“…In both cases, in fact, stability or coaptation of the joint should be guaranteed, although in a different manner, by a synergic activity of both passive and active intra-and periarticular structures. This hypothesis is supported by recent findings that, during a highly dynamic motion such as the landing phase of a jump, showed that the ACL length decreases during flexion by an amount similar to that obtained in the present study [30].…”
Section: Discussionsupporting
confidence: 93%
“…3,9 Investigators [10][11][12] have shown that the ground reaction forces (GRFs) that athletes incur right after foot contact in sharp decelerating motions greatly affect the magnitude of proximal tibial anterior shear forces and ACL loading. Authors 13,14 of in vivo studies who measured the amount of ACL strain during landing tasks demonstrated that the timing of peak ACL strain coincides with the peak GRF that occurs immediately after the foot contact of landing. Taylor et al 13 also demonstrated that knee-flexion angles were inversely related to ACL strain during landing.…”
mentioning
confidence: 99%
“…Authors 13,14 of in vivo studies who measured the amount of ACL strain during landing tasks demonstrated that the timing of peak ACL strain coincides with the peak GRF that occurs immediately after the foot contact of landing. Taylor et al 13 also demonstrated that knee-flexion angles were inversely related to ACL strain during landing. Furthermore, the direction of peak GRF relative to the tibia in the sagittal plane has been reported to substantially affect the amount of net proximal tibial anterior shear forces immediately after the foot contact of landing.…”
mentioning
confidence: 99%
“…Two studies were found that analysed in vivo ACL strain by either combining markerbased motion analysis with MRI-based computational modelling and fluoroscopic imaging 16 , or direct measurements based on an implanted DVRT device 14 . Unfortunately, both in vivo studies were limited to kinematic data without reporting on muscle-tendon forces, and were thus excluded from the review.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%